A REVIEW OF THE EFFECTIVENESS, CONTRIBUTION, AND GROWTH OF REGIONAL TAXES AND CHARGES AS A PILLAR OF FISCAL INDEPENDENCE IN DISTRICT GOVERNMENTS: AN EMPIRICAL STUDY IN KLATEN REGENCY - Puspitasari, Lintang Tri; Siswati, Susi; Panggabean, Jannes Samuel Elfronzo Abhimael (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study examines the effectiveness, contribution, and growth of regional taxes and regional charges as pillars of fiscal independence in Klaten Regency during the 2019–2023 period. Addressing the limited empirical evidence that simultaneously evaluates these three dimensions at the regency level, particularly in non-metropolitan areas, this study provides a comprehensive assessment of local fiscal performance within the framework of regional autonomy. The analysis utilizes secondary data obtained from the Local Government Financial Statements and applies descriptive ratio-based techniques, including effectiveness, contribution, and growth ratios, processed using Microsoft Excel. The findings indicate that both regional taxes and regional charges are classified as highly effective, as realized revenues consistently exceed annual targets. However, contribution analysis reveals a structural imbalance in locally generated revenue, where regional taxes provide a moderate contribution, while regional charges contribute less than 10%, indicating a very weak fiscal role. Furthermore, the growth rates of both revenue sources exhibit considerable volatility and are predominantly categorized as unsuccessful, with annual growth remaining below the 30% benchmark. These results suggest that short-term target achievement does not necessarily translate into sustainable fiscal independence. This study contributes to the fiscal decentralization literature by demonstrating that effectiveness alone is insufficient to support fiscal independence without balanced revenue contributions and stable growth. The findings offer policy-relevant insights for strengthening local fiscal capacity through improved administrative performance, digitalization of revenue collection, and enhanced governance mechanisms.